2001
DOI: 10.1038/35092552
|View full text |Cite
|
Sign up to set email alerts
|

Human presence in the European Arctic nearly 40,000 years ago

Abstract: The transition from the Middle to the Upper Palaeolithic, approximately 40,000-35,000 radiocarbon years ago, marks a turning point in the history of human evolution in Europe. Many changes in the archaeological and fossil record at this time have been associated with the appearance of anatomically modern humans. Before this transition, the Neanderthals roamed the continent, but their remains have not been found in the northernmost part of Eurasia. It is generally believed that this vast region was not colonize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(63 citation statements)
references
References 11 publications
1
59
0
2
Order By: Relevance
“…This agrees with the fact that humans were occupying areas inside the Arctic Circle up to 10ka before the occupation at Kraków Spadzista (e.g. Pavlov et al, 2001;Pitulko et al, 2004), and were not excluded from northern Europe during the LGM period that followed the occupation at Kraków Spadzista (e.g. Street and Terberger, 1999).…”
Section: Humans and Climate At Kraków Spadzista Street (B)supporting
confidence: 74%
See 1 more Smart Citation
“…This agrees with the fact that humans were occupying areas inside the Arctic Circle up to 10ka before the occupation at Kraków Spadzista (e.g. Pavlov et al, 2001;Pitulko et al, 2004), and were not excluded from northern Europe during the LGM period that followed the occupation at Kraków Spadzista (e.g. Street and Terberger, 1999).…”
Section: Humans and Climate At Kraków Spadzista Street (B)supporting
confidence: 74%
“…Yet although early AMH had evolved in warm African climates and therefore lacked specific morphological adaptations to the cold, archaeological sites in Europe have indicated that some of the earliest AMH in Europe were able to colonise regions further north than the native Neanderthals reached in over 200ka (e.g. Mamontovaya Kurya in NW Russia; Pavlov et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The site of Mamontovaya Kurya, located on the Arctic Circle in northern Russia and dating to Ͼ40,000 cal BP, contains artifacts similar to those of Kostenki 12, layer III (53). It may also represent a short-term occupation related to large mammal procurement (and only seasonal use of high latitude areas?…”
Section: Eastern Europementioning
confidence: 99%
“…Thus, glacial ice was not a particular impediment to human travel in the Siberian arctic during the LGM. It is obvious that people were exploiting arctic coastal, or near-coastal, resources early on, with archeological sites dating to between 30,000 and 40,000 years ago in the Russian arctic (e.g., Pitulko et al 2004;Pavlov et al 2001). Nevertheless, archeological evidence for human occupation of interior northeast Siberia from the onset of the LGM over 25 kya until initiation of glacial retreats is effectively absent (Goebel et al 2003).…”
Section: Paleoecologymentioning
confidence: 99%